Processes of Exclusive Inclusion Present in Private Higher Education - Mário Luiz Ferrari Nunes; Marcos Garcia Neira (Universidade Federal do Rio Grande do Sul, 2014)
The local and global pressures for new forms of social organization have focused on public policies aimed at granting access to higher education to a hitherto underprivileged segment of the population. This article deals with the effects that these inclusion processes can produce. The data collected through an ethnographic study in a private institution of higher education (IHE) were analyzed in the light of the concepts of identity and difference as produced by the field of Cultural Studies. The text proposes that the inclusion processes reinforce and validate only the identities that fit the imposition of consumption and performance characteristic of Neoliberalism, and signal this difference through subtle processes of exclusion of those who do not conform to the prevailing social logic.